TAVR in Patients with Left Ventricular Assist Device: Case Report and Literature Review. Issue 1 (2nd January 2019) - Iadanza, Alessandro; D'Ascenzi, Flavio; Torrisi, Andrea; Sinicropi, Giuseppe; Neri, Eugenio; Bernazzali, Sonia; Maccherini, Massimo; Pierli, Carlo
ABSTRACT: The use of left ventricular assist devices (LVADs) as a bridge-to-transplant or destination therapy in patients with end-stage heart failure has been increased during the last years. However, a potential obstacle to the success of long-term LVAD support is represented by the development of de novo aortic valve lesions leading to aortic regurgitation or, more rarely, to commissural fusion and stenosis. The paper addresses the main pathophysiological factors in the development of aortic valvular regurgitation in patients with LVAD and describes an updated review of all transcatheter aortic valve replacement (TAVR) cases to treat aortic regurgitation currently available. We also report on a case of a patient with a Jarvik 2000 requiring transcatheter aortic valve replacement for aortic regurgitation. The procedure was performed using a 31-mm CoreValve prosthesis. The first check after the positioning of the prosthetic valve revealed a good result. However, a second 10-min check, performed as per protocol at the end of the procedure, showed a sliding of the prosthetic valve downward toward the apex of the left ventricle with a severe periprosthetic regurgitation. Therefore, a second 31-mm CoreValve was deployed within the previous valve prosthesis and a 10-min check revealed a stable position and a mild residual leak. The management of LVAD patients with aortic regurgitation remains challenging. Although transcatheter techniques have demonstrated feasibility in these patients, technical adjustments and further expertise are needed to optimize these procedures.